Electrocatalytic oxidation of amitrole and diuron on iron(II) tetraaminophthalocyanine-single walled carbon nanotube dendrimer - Mugadza, Tawanda; Nyokong, Tebello (Elsevier, 2016)
FeTAPc-single walled carbon nanotube (SWCNT) dendrimers are employed as glassy carbon electrode modifiers for the electrocatalytic oxidations of amitrole and diuron. The catalytic rate constants were 4.55 × 103 M−1 s−1 and 1.79 × 104 M−1 s−1 for amitrole and diuron, respectively using chronoamperometric studies. The diffusion constants were found to be 1.52 × 10−4 cm2 s−1 and 1.91 × 10−4 cm2 s−1 for diuron and amitrole, respectively. The linear concentration range for both were from 5.0 × 10−5 to 1.0 × 10−4 M and sensitivities of 0.6603 μA/μM and 0.6641 μA/μM for amitrole and diuron, with corresponding limits of detection of 2.15 × 10−7 and 2.6 × 10−7 M using the 3δ notation, respectively.